2017
DOI: 10.1680/jgein.16.00025
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of multiwall carbon nanotubes through a high-density polyethylene geomembrane

Abstract: The new applications for carbon nanotubes (CNTs) in various fields and consequently their greater production volume have increased their potential release to the environment. Landfills are one of the major locations where carbon nanotubes are expected to be disposed and it is important to ensure that they can limit the release of CNTs. Diffusion of multiwall carbon nanotubes (MWCNTs) dispersed in an aqueous media through a high-density polyethylene (HDPE) geomembrane (as a part of the landfill barrier system) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…For example, elemental techniques based on measuring carbon to quantify CNMs (e.g., total organic carbon analysis or thermal optical transmittance) will have a lowest achievable detection limit at the concentration for detecting total carbon. 63, 79,152154 A similar relationship exists for techniques based on elemental concentration measurements of metal-based ENMs (e.g., ICP-MS). An exception is spICP-MS, which can detect individual ENMs as a result of the substantially shorter dwell times (50 μs to 10 ms) compared to total elemental analysis (approximately 300 ms).…”
Section: Evaluation Of Detection Limits For Different Analytical Methodsmentioning
confidence: 73%
“…For example, elemental techniques based on measuring carbon to quantify CNMs (e.g., total organic carbon analysis or thermal optical transmittance) will have a lowest achievable detection limit at the concentration for detecting total carbon. 63, 79,152154 A similar relationship exists for techniques based on elemental concentration measurements of metal-based ENMs (e.g., ICP-MS). An exception is spICP-MS, which can detect individual ENMs as a result of the substantially shorter dwell times (50 μs to 10 ms) compared to total elemental analysis (approximately 300 ms).…”
Section: Evaluation Of Detection Limits For Different Analytical Methodsmentioning
confidence: 73%
“…-15 m 2 /s (Saheli et al 2017). In addition to these laboratory-scale tests, Saheli et al (2017) modelled different scenarios with HDPE geomembranes and geosynthetic clay liners and concluded that such technical barriers are effective for MWCNTs. However, it should be noted that worldwide there are many open landfills and dumps without any engineered barrier.…”
Section: Potential Nanoemissions From Landfill Sitesmentioning
confidence: 99%
“…Mcwatters et al [ 7 ] further showed that the breakthrough time of organic chemical transport through a GM was only 24 h, and the pollutant flux reached a steady state after approximately one week. In contrast, Saheli et al [ 8 ] showed that inorganic pollutants cannot diffuse through the GM. Therefore, the diffusion of organic pollutants through GM is the focus of most studies.…”
Section: Diffusion Of Pollutants Through Gm/gcl/almentioning
confidence: 97%